CORPORATE GOVERNANCE, TAX AVOIDANCE, AUDIT DELAY DAN NILAI PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN PERBANKAN DI BEI PERIODE 2010-2014) - Ronald Tehupuring (Universitas Trunojoyo Madura, 2016)
Corporate governance is an issue related to the practice of tax avoidance and audit delay and will impact on the value of firm. Application of corporate governance expected to mitigate the asymmetry of information and increase the confidence of shareholders. This study aimed to examine the relationship of corporate governance and tax evoidance practices and their effect on audit delay and firm value. Samples were obtained through purposive sampling and as many as 130 observations, after deducting the data outliers, the final sample of 125 observations 2010-2014 of corporate banking listed on the Indonesian Stock Exchange. The data analysis technique used is multiple linear regression with SPSS version 17. The results show that the first model: reputation, of KAP, audit quality, and audit committee has no effect on tax avoidance, while independent commissioner negative effect on tax avoidance; The second model suggests that tax avoidance and independent commissioner has no effect on audit delay, while the audit committee negatively affect audit delay; The third model shows that tax avoidance (negative) and the audit committee (positive) effect on the value of firm, while the independent commissioner has not affect on value of firm.